High concentrations of plastic hidden beneath the surface of the Atlantic Ocean - Katsiaryna Pabortsava (Nature Portfolio, 2020)
The risks posed by plastic contamination of the ocean cannot be assessed as their amount and location remain largely unknown. Here the authors show that large quantities of microplastics exist below the ocean surface over the entire Atlantic in quantities greater than previously estimated.